The role of networks in the commercialisation of rural weavers of Northern Kwazulu-Natal in South Africa - Sefoko, Ngwako Moses (2013)
This study identifies intra- and inter-organisational barriers to commercialisation 0f rural weavers in KwaZulu-Natal and evaluate the role of local networks in procurement, processing and marketing activities in order to reduce transaction costs. The study specifically investigates the way local networks a san alternative organisational mode can become a solution to minimise transaction costs of rural weavers. The expectation is that weaving groups incur less transaction costs during commercialisation when they have well established local networks. This follows as transaction costs give a reflection of the market given the operating environment. The access to market information, assets, extension services and remunerative markets is of commercial importance. An exploratory analysis suggests that existing networks in craft businesses in northern KwaZulu-Natal have an impact in reducing some of the transaction costs of weavers, thereby improving weavers' economic performance and commercialisation process. Local networks have therefore shown to be not only a pre-condition for non-local networks, but an important vehicle for information exchange, co-ordination of fragmented activities, conducting training services, and guarding against market failures for weavers. However, the two fundamental questions to be asked for future research are how to create local networks to improve supply chain functions in similar or different socio-economic settings to this study's cases and how to assure the sustainability of networks. === Dissertation (Magister Institutionis Agrariae)--University of Pretoria, 2006. === Agricultural Economics, Extension and Rural Development === unrestricted